Pengaruh Sharia Compliance dan Non Performing Financing terhadap Nilai Perusahaan (Studi Empiris Pada Perbankan Syariah) - Erliati Siregar; Nil Firdaus; Anggi Kartika (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study used the help of eviews 10 software as a data analysis tool. The population in this study are all Islamic Commercial Banks registered with the Financial Services Authority (OJK) during the 2018-2022 period. Sampling in this study used purposive sampling in order to obtain 7 Islamic Commercial Banks as samples in this study. The results of the study partially show that the IIR proxy for Sharia Compliance variable for NP obtained a tcount of -0.190307. tcount (-0.190307) < ttable (1.69552), the conclusion is that partially IIR has no significant negative effect on NP. The Sharia Compliance proxy ZPR variable for NP obtained a tcount of -1.772808. tcount (-1.772808) < ttable (1.69552), the conclusion is that partially ZPR has no significant negative effect on NP. The NPF variable on NP obtained a tcount of -2.658745. tcount (-2.658745) < ttable (1.69552), the conclusion is that partially NPF has a significant negative effect on NP. Based on the table above shows the R-Squared of 0.776780 or equal to 77.67%. This means that the variables IRR, ZPR and NPF are able to explain the NP of 77.67% while the remaining 22.33% is explained by other variables not included in this model. This means that there are other variables that explain the disclosure of NP in the company's annual report.